2023
DOI: 10.1186/s12886-022-02759-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel surgical approach for fixation of a posterior chamber intraocular lens of Rayner 620 H with Gore-Tex suture

Abstract: Purpose To report a novel surgical approach for the scleral fixation of the Rayner 620 H intraocular lens (IOL) with Gore-Tex suture and its outcomes at 6 months postoperatively. Methods 19 consecutive patients who underwent novel surgical approach for the scleral fixation of Rayner 620 H IOL with Gore-Tex suture at Peking Union Medical College Hospital between June 2020 and June 2021 were included. Data on best-corrected visual acuity (BCVA), sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Finally, this technique was also applicable to the scleral xation of astigmatic IOL due to another electrocoagulation xation technique of IOL loop we proposed previously. 10 The most common cause of IOL scleral xation in our observation was aphakia (11 eyes, 68.75%), which was similar to Zhang Y et al's report (18 eyes, 100%), 1 but different from Wang T et al's report, 7 which believed that the most common cause was subluxated/dislocated lens. The traditional view was that the three-piece polymethyl methacrylate IOL was more suitable for scleral xation due to the greater elasticity of the loop, but the three-piece IOL needed to be knotted and xed with suture, [17][18][19][20] which had the risk of tilt or eccentricity of IOLs due to the suture knot shift in the long term.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Finally, this technique was also applicable to the scleral xation of astigmatic IOL due to another electrocoagulation xation technique of IOL loop we proposed previously. 10 The most common cause of IOL scleral xation in our observation was aphakia (11 eyes, 68.75%), which was similar to Zhang Y et al's report (18 eyes, 100%), 1 but different from Wang T et al's report, 7 which believed that the most common cause was subluxated/dislocated lens. The traditional view was that the three-piece polymethyl methacrylate IOL was more suitable for scleral xation due to the greater elasticity of the loop, but the three-piece IOL needed to be knotted and xed with suture, [17][18][19][20] which had the risk of tilt or eccentricity of IOLs due to the suture knot shift in the long term.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, it was found that among all the population who received secondary IOL implantation, men accounted for a higher proportion, with an average age of about 60 years, similar to previous literature reports. 7,8 As for the selection of suture, 10 − 0 suture was often used for scleral xation of IOL in the early stage. 4,5 However, as time went on, the complications related to too thin/degradable 10 − 0 polypropylene suture such as suture erosion and fracture became more and more prominent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations